Licenciamento automático de projectos: uma solução para um problema de cooperação? - João Poças Martins (2009)
Information management in the construction industry is inefficient when compared with other activities. The construction industry lacks standard formats for the representation of building products, which would allow efficient and, in some cases, automatic communication. Although different information models have been proposed over the last decades, their adoption has been scarce. The diffusion of these models throughout the construction industry is hindered by a cooperation problem: the cumulative benefits de-rived from widespread BIM adoption are clearly larger than those that can be achieved through individual adoption, so the incentives to change work processes are small. Automated code checking performed upon designs that follow standard representation formats is regarded as a demonstration of the immediate benefits that can be obtained by users who voluntarily adopt this kind of information technology. An information model and an application developed at FEUP are briefly presented. These tools perform automated code checking of domestic water systems for compliance with the main national regulations.